2005
DOI: 10.1101/gr.2807605
|View full text |Cite
|
Sign up to set email alerts
|

Classification of a large microarray data set: Algorithm comparison and analysis of drug signatures

Abstract: A large gene expression database has been produced that characterizes the gene expression and physiological effects of hundreds of approved and withdrawn drugs, toxicants, and biochemical standards in various organs of live rats. In order to derive useful biological knowledge from this large database, a variety of supervised classification algorithms were compared using a 597-microarray subset of the data. Our studies show that several types of linear classifiers based on Support Vector Machines (SVMs) and Log… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
63
0

Year Published

2006
2006
2016
2016

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 105 publications
(65 citation statements)
references
References 23 publications
2
63
0
Order By: Relevance
“…This connection of traditional and novel data provides context and meaning to the alterations in gene expression caused by a candidate drug or chemical (Amin et al, 2002;Bushel et al, 2002;Hamadeh et al, 2002aHamadeh et al, , 2002bSteiner et al, 2004;Fielden et al, 2005;Ruepp et al, 2005). Further, this database has been mined using rigorous, statistical approaches based on sophisticated classification algorithms and logistic regression producing a library of linear, robust binary classifiers (Ganter et al, 2005;Natsoulis et al, 2005). These classifiers can be used to characterize, diagnose, and predict pharmacologic and toxicologic properties using gene expression data (Steiner et al, 2004;Ganter et al, 2005.…”
Section: Introductionmentioning
confidence: 99%
“…This connection of traditional and novel data provides context and meaning to the alterations in gene expression caused by a candidate drug or chemical (Amin et al, 2002;Bushel et al, 2002;Hamadeh et al, 2002aHamadeh et al, , 2002bSteiner et al, 2004;Fielden et al, 2005;Ruepp et al, 2005). Further, this database has been mined using rigorous, statistical approaches based on sophisticated classification algorithms and logistic regression producing a library of linear, robust binary classifiers (Ganter et al, 2005;Natsoulis et al, 2005). These classifiers can be used to characterize, diagnose, and predict pharmacologic and toxicologic properties using gene expression data (Steiner et al, 2004;Ganter et al, 2005.…”
Section: Introductionmentioning
confidence: 99%
“…[29] profiles which contains 301 samples with 6316 variables (genes). The other data set is the Iconix microarray data set (denoted as Iconix) from drug treated rat livers [41] which contains 255 samples with 10455 variables.…”
Section: Comparison Of Admm and Pgadm On Synthetic Datamentioning
confidence: 99%
“…In the recent past there has been a growing interest in analysis of interval-valued data in the learning community [1,2]. In many real world problems it is not possible to describe the data by a precise value but intervals may be a more proper description.…”
Section: Introductionmentioning
confidence: 99%
“…Also in the case of gene-expression data like micro-array, since the experiments are usually noisy and data is prone to be erroneous, data for a number of replicates of the same experiment are provided. Past research has shown that handling uncertainty in such applications by the representation as interval data leads to accurate learning algorithms [3,1]. Classification formulations which are capable of handling interval data have immense importance from a pragmatic perspective.…”
Section: Introductionmentioning
confidence: 99%